MANAGEMENT OF CHANGES IN UKRAINIAN HIGHER EDUCATION INSTITUTIONS IN THE CONDITIONS OF EUROPEAN INTEGRATION, TAKING INTO ACCOUNT THE CRISIS AND ENSURING THE REQUIREMENTS OF SUSTAINABLE DEVELOPMENT - GONCHAR, Olga; DIKHAMINJIA, Irma (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The processes of globalization of higher education, the European Educational Space impose requirements on universities that they must meet. However, the conditions of modern educational and scientific activity in Ukraine do not always allow for the prompt and comprehensive implementation of these standards. In practice, partial modernization of individual educational processes often takes place without a deep systemic renewal. That is why strategic management of changes in the educational and scientific space should become the center of a new model of university development. The article examines the modern educational and scientific environment, identifies the main factors that shape the challenges and crises of higher education institutions in Ukraine in the context of modern processes of internationalization. The main parameters of the concept of change management in higher education institutions in the context of European integration and crises are characterized. Practical examples of change management at Khmelnytskyi National University are given, which clearly demonstrate that sustainable renewal occurs, provided that there is an internal institutional desire for development, when transformation is accompanied not only by management tools, but also by a culture of change. It is concluded that there is no ideal change management model suitable for each HEI, but there are principles that can be general: openness, systematicity, responsibility, strategic vision, ability to reflect. The success of change management and the effectiveness of the HEI management concept itself are possible if changes are considered as a consistent, structured and, at the same time, adaptive process that combines analysis, vision, management architecture, implementation and adaptation.